Two-Dimensional Shear-Wave Elastography of the Thyroid in Clinically Healthy Dogs in Different Age Groups - Ramos, Denise Jaques [UNESP]; Disselli, Tamiris; Gomes, Diego Rodrigues; Aires, Luiz Paulo Nogueira [UNESP]; Tinto, Stéfany Tagliatela; Salazar, Diana Villa Verde; Pereira, Mariane Magno Ferreira; Miranda, Brenda Santos Pompeu de [UNESP]; Oliveira, Ana Paula Luiz de [UNESP]; Lima, Bruna Bressianini [UNESP]; Uscategui, Ricardo Andres Ramirez; Feliciano, Marcus Antônio Rossi (MDPI, 2024)
The thyroid of dogs has not been extensively studied in 2D shear-wave elastography, making it challenging to apply this technique in the diagnosis of thyroid diseases in a non-invasive manner. The aim of this study is to evaluate the thyroid glands of healthy dogs using 2D shear-wave elastography in order to establish qualitative and quantitative parameters of tissue stiffness in dogs in different age groups. A total of 31 dogs of various breeds, sexes, and sizes were evaluated. Animals with clinical signs or ultrasound findings indicative of endocrine disease or thyroid lesions were excluded from the study. The shear-wave velocity data in meters per second (m/s) and color elastograms were evaluated and calculated using QelaXto™ 2D software. A healthy thyroid exhibits a blue-color elastogram, indicative of low stiffness. The reference range for the shear-wave velocity of thyroid tissue assessed by 2D shear-wave elastography can be between 1.6 and 2.0 m/s, with a variation of ±0.889 in adult and senior dogs.
Keywords: diagnostic imaging; dogs; elastography; stiffness; thyroid; ultrasound